Delivery of 5-Aza-2′-Deoxycytidine to Cells Using Oligodeoxynucleotides - Yoo, Christine B.; Jeong, Shinwu; Egger, Gerda; Liang, Gangning; Phiasivongsa, Pasit; Tang, Chunlin; Redkar, Sanjeev; Jones, Peter A. (Cancer research (Chicago, Ill.), 2007)
The major goal of epigenetic therapy is to reverse aberrant promoter hypermethylation and restore normal function of tumor suppressor genes by the use of chromatin-modifying drugs. Decitabine, or 5-aza-2′-deoxycytidine (5-aza-CdR), is a well-characterized drug that is now Food and Drug Administration approved for the treatment of myelodysplastic syndrome. Although 5-aza-CdR is an extremely potent inhibitor of DNA methylation, it is subject to degradation by hydrolytic cleavage and deamination by cytidine deaminase. We show that short oligonucleotides containing a 5-aza-CdR can also inhibit DNA methylation in cancer cells at concentrations comparable with 5-aza-CdR. Detailed studies with S110, a dinucleotide, showed that it works via a mechanism similar to that of 5-aza-CdR after incorporation of its aza-moiety into DNA. Stability of the triazine ring in aqueous solution was not improved in the S110 dinucleotide; however, deamination by cytidine deaminase was dramatically decreased. This is the first demonstration of the use of short oligonucleotides to provide effective delivery and cellular uptake of a nucleotide drug and protection from enzymatic degradation. This approach may pave the way for more stable and potent inhibitors of DNA methylation as well as provide means for improving existing therapeutics. [Cancer Res 2007;67(13):6400–8]